In-situ construction of an alloy hybrid interface and ultrathin ZnS nanosheets catalyst for polysulfide by trifunctional ZnI2 electrolyte additive for Li-S batteries - Zhao, Zehua; Desalegn, Bezawit Z.; Joe, Hye Jeong; Kim, Seok Ki; Yoo, Jungho; Wang, Deyu; Seo, Jeong Gil (Energy Storage Materials, 2024)
Lithium-sulfur batteries (LSBs) are considered promising candidates for next-generation energy storage devices owing to their ultrahigh theoretical energy density. However, LSBs are hindered by uncontrollable lithium dendrite growth, polysulfides shuttle effects, and sluggish sulfur kinetics. Herein, this work develops a multifunctional ZnI2 electrolyte additive for LSB for local high concentration base electrolyte. At anode side, a LixZn alloy hybrid interface leading to planar deposited lithium is formed from the reaction between Li metal and the ZnI2 additive and reduction products of Li+ solvation shell of the electrolyte. Moreover, planar deposited lithium was confirmed by in-situ liquid transmission electron microscopy (TEM). For cathode side, Zn2+ under the drive of electric field prior react with lithium polysulfide to form ultrathin ZnS nanosheets exposed with (100) miller index serving as a catalyst to accelerate sulfur redox kinetics and inhibit polysulfides shuttling. Consequently, the LSB with ZnI2 additive exhibits a remarkable discharge capacity of 712 mA h g−1 at 0.5 C after 300 cycles and a superior rate capability of 674.9 mA h g−1 at 2 C. This work demonstrates that ZnI2 serves as a multifunctional electrolyte additive to simultaneously facilitate the sulfur redox kinetics, reduce the shuttle effect, and promote smooth Li growth.
Keywords: Electrolyte additives; Hybrid interface; In-situ liquid transmission electron microscopy; Lithium/sulfur batteries; Multifunctional electrolyte additive; Multifunctionals; Polysulphides; Solid electrolyte interphase; Transmission electron; Ultra-thin; In-situ liquid TEM; Lithium-sulfur battery; Multifunctional electrolyte additive; Solid electrolyte interphase